2021
DOI: 10.1007/s10661-021-09447-7
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposure levels to O3, NOx and PM10 and the association to ambient levels in two Swedish cities

Abstract: Exposure to air pollution is of great concern for public health although studies on the associations between exposure estimates and personal exposure are limited and somewhat inconsistent. The aim of this study was to quantify the associations between personal nitrogen oxides (NOx), ozone (O3) and particulate matter (PM10) exposure levels and ambient levels, and the impact of climate and time spent outdoors in two cities in Sweden. Subjects (n = 65) from two Swedish cities participated in the study. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Furthermore, studies have shown central monitoring stations to be a reasonable proxy for personal exposure to birch pollen [ 42 ]. Also, monitoring station data correlated well with personal exposure in the study [ 27 ]. The panel data collected both in, and outside, pollen season ensured a substantial exposure contrast.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Furthermore, studies have shown central monitoring stations to be a reasonable proxy for personal exposure to birch pollen [ 42 ]. Also, monitoring station data correlated well with personal exposure in the study [ 27 ]. The panel data collected both in, and outside, pollen season ensured a substantial exposure contrast.…”
Section: Discussionmentioning
confidence: 64%
“…Birch pollen counts were obtained from centrally located pollen monitoring stations using standard methods [ 26 ]. Ambient concentrations of the air pollutants NO x , O 3 and PM 2.5 , and meteorological data of relative humidity and temperature were measured at centrally located fixed monitoring stations in the two study centers and obtained from the environmental authorities as previously described [ 27 ]. In this study, we used PM 2.5 as this was available in both locations for the study period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of secondary PM 10 particles is unlikely (because it requires ambient environmental conditions favourable to GPC conditions), so there might been some common sources of PM and NO X (like vehicles). Multiple studies have showed similar ndings (Haga et al, 2021;Rodriguez et al, 2019). Nitrogen Family (NO X , NO, NO 2 ) showed signi cant positive correlation among three, with highest correlation between NO and NO X (0.87), followed by NO 2 and NO X (0.83), and NO and NO 2 (0.58).…”
Section: Correlograms Of Pollutants At Dharuhera Sitementioning
confidence: 60%
“…In last years, urbanization and industrialization have been major contributing factors to poor air quality. As the air quality deteriorates, exposure to air pollution remains a fundamental concern to public health: chemical species in the atmosphere, such as NO2, SO2, CO, PM10, PM2.5, C6H6, could severely damage the health of the population (Breton et al, 2021;Haga et al, 2021).…”
Section: Introductionmentioning
confidence: 99%